Financial institutions - International Finance Corporation (Washington D.C. : International Finance Corporation, 1998)
This report sums up the lessons IFC has learned in its 27 years of advising and investing in financial institutions of all kinds in the developing world
osc 18/05/18, ijb 11/03/2019
Loans
Keywords: Financial Institutions management